Biomarkers for Diagnosis and Prediction of Outcomes in Contrast-Induced Nephropathy - Justor Banda; Raquel Duarte; Therese Dix-Peek; Caroline Dickens; Pravin Manga; Saraladevi Naicker (International Journal of Nephrology)
Background. Serum creatinine is suboptimal as a biomarker in the early diagnosis of contrast-induced nephropathy (CIN). In this study, we investigated a panel of novel biomarkers in the early diagnosis of CIN and in assessing patient outcomes. Methods. This single-centre, nested, prospective case-controlled study included 30 patients with CIN and 60 matched controls. Serum and urine samples were collected before contrast administration and at 24 hours, 48 hours, and ≥5 days after contrast administration. Concentrations of NGAL, cystatin C, β2M, IL18, IL10, KIM1, and TNFα were determined using Luminex and ELISA assays. Outcomes were biomarker diagnostic discrimination performance for CIN and mortality after generation of area under receiver operating characteristic curves (AUROCs). Results. Median serum levels for 24 h cystatin C (p<0.01) and 48 h β2M levels (p<0.001) and baseline urine NGAL (p=0.02) were higher in CIN patients compared to controls with AUROCs of 0.75, 0.78, and 0.74, respectively, for the early diagnosis of CIN. Serum β2M levels were higher in CIN patients at all time points. Elevated baseline serum concentrations of IL18 (p<0.001), β2M (p=0.04), TNFα (p<0.001), and baseline urine KIM (p=0.01) and 24 h urine NGAL (p=0.02) were significantly associated with mortality. Baseline serum concentrations of IL18, β2M, and TNFα showed the best discrimination performance for mortality with AUROCs, all >0.80. Baseline NGAL was superior for excluding patients at risk for CIN, with positive and negative predictive ranges of 0.50–0.55 and 0.81–0.88, respectively. Cystatin C (p=0.003) and β2M (p=0.03) at 24 h independently predicted CIN risk. β2M predicted increased mortality of 40% at baseline and 50% at 24 hours. Conclusion. Serum cystatin C at 24 h was the best biomarker for CIN diagnosis, while baseline levels of serum IL18, β2M, and TNFα were best for predicting prognosis.